Resilience testing of health systems - Rogers, Heather L (2021)
The resilience of health systems has received considerable attention as of late, yet little is known about what a resilience test might look like. We develop a resilience test concept and methodology. We describe key components of a toolkit and a 5-phased approach to implementation of resilience testing that can be adapted to individual health systems. We develop a methodology for a test that is balanced in terms of standardization and system-specific characteristics/needs. We specify how to work with diverse stakeholders from the health ecosystem via participatory processes to assess and identify recommendations for health system strengthening. The proposed resilience test toolkit consists of "what if" adverse scenarios, a menu of health system performance elements and indicators based on an input-output-outcomes framework, a discussion guide for each adverse scenario, and a traffic light scorecard template. The five phases of implementation include Phase 0, a preparatory phase to adapt the toolkit materials; Phase 1: facilitated discussion groups with stakeholders regarding the adverse scenarios; Phase 2: supplemental data collection of relevant quantitative indicators; Phase 3: summarization of results; Phase 4: action planning and health system transformation. The toolkit and 5-phased approach can support countries to test resilience of health systems, and provides a concrete roadmap to its implementation.